THE INFLUENCE OF SERVICE QUALITY TOWARDS STUDENT’S SATISFACTION AT ACADEMIC ADMINISTRATION AND STUDENTS AFFAIRS DEPARTMENT (AASA) - Ekosulis Ekosulis (Fakultas Teknik Universitas Maritim AMNI Semarang, 2022)
Institute of Business and Informatics STIKOM Surabaya (STIKOM Surabaya) is one of the private universities in Surabaya. STIKOM Surabaya has two faculties namely Faculty of Technology and Informatics, and Faculty of Economics and Business. The Faculty of Technology and Informatics has six departments, while the Faculty of Economics and Business has three departments. The department handling academic administration of students from all departments is Academic Administration and Student Affairs Department (AASA). The problem arises is STIKOM Surabaya had a will to evaluate the service quality in AASA based on student’s perceptions which would be used as an input to improve the service quality of AASA